2021
DOI: 10.3389/fpls.2021.650609
|View full text |Cite
|
Sign up to set email alerts
|

From Microbial Dynamics to Functionality in the Rhizosphere: A Systematic Review of the Opportunities With Synthetic Microbial Communities

Abstract: Synthetic microbial communities (SynComs) are a useful tool for a more realistic understanding of the outcomes of multiple biotic interactions where microbes, plants, and the environment are players in time and space of a multidimensional and complex system. Toward a more in-depth overview of the knowledge that has been achieved using SynComs in the rhizosphere, a systematic review of the literature on SynComs was performed to identify the overall rationale, design criteria, experimental procedures, and outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 114 publications
(184 reference statements)
0
26
0
2
Order By: Relevance
“…Recent studies concerning synthetic microbial communities (SynComs) aim to expand the current application strategies of single and multispecies inocula ( de Souza et al, 2020 ; Marín et al, 2021 ). SynComs are composed of PGPR species and strengthened with both accessory and keystone species to obtain a robust diversity and maintain the functional stability, respectively ( Sánchez-Cañizares et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies concerning synthetic microbial communities (SynComs) aim to expand the current application strategies of single and multispecies inocula ( de Souza et al, 2020 ; Marín et al, 2021 ). SynComs are composed of PGPR species and strengthened with both accessory and keystone species to obtain a robust diversity and maintain the functional stability, respectively ( Sánchez-Cañizares et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al ( 2021 ) investigated the differences between Chinese wheat yellow mosaic resistant and susceptible wheat root endosphere and rhizosphere microbial, and the results revealed that beneficial rhizosphere microbes, such as Xanthomonadales, Actinomycetales, Sphingomonas, Rhizobium, Bacillaceae, Bacillus, Streptomycetaceae, Streptomyces, Nocardioides, Pseudonocardia, Bradyrhizobium, Pseudonocardiaceae , and Solibacteraceae , were enriched in the resistant wheat root. Some studies revealed that potential beneficial microbes, such as Bacillus, Paenibacillus, Streptomyces, Pseudomonas, Flavobacterium, Arthrobacter, Rhizobium, Microbacterium, Micrococcous , and Burkholderia , can establish disease suppression by a single strain or SynComs (synthetic microbial communities) via an antagonistic effect to protect the host from pathogens' invasion and attack (Weller et al, 2002 ; Lee et al, 2021 ; Li et al, 2021c ; Marín et al, 2021 ). In this study, Streptomyces, Azospirillum , and Bacillus were identified as the potentially beneficial bacterial genera; some studies show that species within these genera can be used to biocontrol strawberry anthracnose; other beneficial microbes, such as Chromobacterium, Caulobacter, Paenibacillus, Enterobacter, Arthrobacter, Azoarcus, Microbacterium, Pantoea, Flavobacterium , and Pseudomonas , were also detected in rhizosphere soils, and their relative abundances were changed after plants were infected by pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Confirmation of this type of results by applying the more definitive LC–MS method to determine the identity and quantity of auxin(s) that are being produced would be important. Future work to quantify the concentration of DAB-derived IAA produced in vivo will be invaluable for creating synthetic DAB communities and understanding how they can be deployed to improve duckweed growth [ 45 ].…”
Section: Discussionmentioning
confidence: 99%